Personal Pensions in the USSR: from the History of the Social Policy of the Soviet State - V. N. Mamyachenkov (Научный диалог, 2018)
The relevance of the article is due to the fact that the problem of pension coverage of the population of the Russian Federation has not lost its topicality today. It is paid attention to the history of the emergence and development of the institute of personal pensions in the USSR. It is argued that the development of pension issues was not encouraged in the former USSR. It is emphasized that even today we are experiencing a shortage of research on pension issues, especially those based on regional materials. Archival materials in the documentary base. The author dwells on the letters of request of citizens of the Middle Urals in the commission for the appointment of personal pensions. It proves that citizens who have (as they thought) certain services “to the party and the state” demanded to be given a personal pension. It is stated that personal pensions had a rather high status, were subject to prestige and were valued for the benefits obtained with their help. It is concluded that the main owners of personal pensions were representatives of the so-called “nomenclature” - party and economic leaders of various ranks.